2008
DOI: 10.1007/s12230-008-9063-x
|View full text |Cite
|
Sign up to set email alerts
|

Leafhoppers (Homoptera: Cicadellidae) Associated with Potatoes in Alaska: Species Composition, Seasonal Abundance, and Potential Phytoplasma Vectors

Abstract: Leafhopper transmitted phytoplasma diseases are an emerging problem for potato and vegetable producers in the conterminous US. Due to its geographical isolation and climatic constraints, Alaska is considered relatively free of diseases and insect pests; therefore growers in the state are exploring the potential of producing seed potato for export. However, the biology of agricultural insect pests in the circumpolar region is lacking or poorly understood. Research conducted from 2004 to 2006 in the main potato … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Although no published reports are available on bumble bee population dynamics in Alaska's major agricultural areas to compare with our results, working with other taxa, Pantoja et al (Pantoja et al 2009, Pantoja et al 2010b, Pantoja et al 2010a) reported a similar pattern of higher relative densities of leafhoppers (Cicadellidae) and wireworms (Elateridae) in Delta Junction relative to Fairbanks and Palmer. Pantoja et al (Pantoja et al 2009, Pantoja et al 2010a, Pantoja et al 2010b) suggested that the differences in relative leafhopper and wireworm densities were associated with climatic differences, cropping histories, habitat availability, or agronomic practices.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although no published reports are available on bumble bee population dynamics in Alaska's major agricultural areas to compare with our results, working with other taxa, Pantoja et al (Pantoja et al 2009, Pantoja et al 2010b, Pantoja et al 2010a) reported a similar pattern of higher relative densities of leafhoppers (Cicadellidae) and wireworms (Elateridae) in Delta Junction relative to Fairbanks and Palmer. Pantoja et al (Pantoja et al 2009, Pantoja et al 2010a, Pantoja et al 2010b) suggested that the differences in relative leafhopper and wireworm densities were associated with climatic differences, cropping histories, habitat availability, or agronomic practices.…”
Section: Discussionsupporting
confidence: 74%
“…Pantoja et al (Pantoja et al 2009, Pantoja et al 2010a, Pantoja et al 2010b) suggested that the differences in relative leafhopper and wireworm densities were associated with climatic differences, cropping histories, habitat availability, or agronomic practices. Bumble bee diversity and abundance can be affected by the availability of floral resources and nest sites, climatic conditions, presence of invasive species, habitat fragmentation, parasitic spillover, urbanization, competition, and the use of pesticides (Cane and Tepedino 2001,Roubik 2001, Goulson et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, their presence has been substantial enough to warrant decades of research. The bulk of animal pest research addresses insects, such as aphids or flies, which are common in the circumpolar North (Johansen, 1999;Johansen and Meadow, 2006;Pantoja et al, 2010b) and have affected Alaskan agriculture.…”
Section: Crop Protectionmentioning
confidence: 99%
“…There are some known challenges in controlling pests that infiltrate Alaskan farms (Stevenson et al, 2014a), although knowledge of agricultural insect pests, weeds, and diseases in the circumpolar region is lacking, and their occurrence and biology are poorly understood (Pantoja et al, 2009(Pantoja et al, , 2010a. Furthermore, agrochemicals used to kill pests, weeds, and disease can linger in the soils of cold environments longer than in warmer areas because the activity of soil bacteria to degrade them is generally slower in colder areas.…”
Section: Integrating Specific Pest Management Strategiesmentioning
confidence: 99%
“…Research conducted from 2004 to 2006 in the main potato production areas of Alaska resulted in the documentation of species composition, abundance, and incidence of pests-for example, 41 leafhopper species, associated with agricultural settings-and the best time to sample them (Pantoja et al, 2009). The information on aphid abundance can be used to move planting dates to avoid aphid incidence, although because of the short growing season, it is not known if this practice will be feasible in Alaska.…”
Section: Integrating Specific Pest Management Strategiesmentioning
confidence: 99%